Documentation of Childbirth Care as Legal Protection for Midwives' Independent Practices - Istri Yuliani (Universitas Katolik Soegijapranata Semarang, 2020)
Abstract: Sixty-two point seven per cent (62.7%) childbirths in Indonesian were handled by midwives. Most of them were in the location of midwife independent practice. It is a critical period during labour. At this time complication may occur. Sometimes the complication is known long before the labour. The patients feel harmed by the complication. Sometimes they bring the cases before the law. One of the ways to prove whether the complication occurs because the process of labour is by analyzing the process of labour by examining the midwifery care documentation. This study aims to see whether the midwifery documentation can provide legal protection to midwives.Descriptive a qualitative study with a combination approach of normative and empirical legal study. The informants were independent practice midwives, Indonesian Midwives Association Committee, midwives in a community health centre. The samples were purposive. Data were collected with an in-depth interview, observation, and documentation study. Data were analyzed with qualitative technique.The record of subjective and objective data of the childbirth care is incomplete. It does not meet the standards of the midwifery documentation. It does not yet have a function as a legal responsibility and accountability.Midwifery documentation made by self-practice midwives has not provided legal protection.Keywords: documentation, midwife, labour, legal Abstrak: Di Indonsia 62,7% persalinan ditolong oleh bidan, tempat persalinan terbanyak (29%) adalah pada praktik mandiri bidan. Masa sekitar persalinan merupakan puncak risiko mortalitas ibu, dimana pada masa ini secara tiba-tiba sering terjadi komplikasi. Kadang kala komplikasi diketahui jauh setelah masa persalinan. Akibat dari komplikasi dan pasien merasa dirugikan, tidak sedikit pasien yang menggugat bidan melalui jalur hukum. Salah satu cara untuk membuktikan apakah komplikasi itu timbul akibat proses persalinan, maka sumber ingatan yang paling tepat yang dapat digunakan untuk menganalisis proses persalinan adalah dengan melihat kembali dokumentasi asuhan kebidanan. Penelitian ini bertujuan untuk mengetahui apakah dokumentasi kebidanan dapat memberikan perlindungan hukum bagi bidan?Jenis penelitian deskriptif kualitatif, dengan pendekatan kombinasi dari penelitian hukum normatif dan penelitian hukum sosiologis empiris. Informan adalah : bidan praktik mandiri, Pengurus IBI, bidan Puskesmas. Pengambilan sampel dengan purposive sampling. Pengumpulan data dengan in-depth interview, observasi dan studi dokumentasi. Analisis data menggunakan teknik analisis kualitatif.Penulisan data subyektif dan obyektif pada asuhan persalinan masih kurang lengkap, belum memenuhi standar penulisan dokumentasi kebidanan, dan belum memiliki fungsi sebagai tanggung jawab dan tanggung gugat secara hukum. Dokumentasi kebidanan oleh praktik mandiri bidan belum dapat memberikan perlindungan hukum. Kata Kunci: dokumentasi, bidan, persalinan, hukum